Implementasi Pengembangan Aplikasi Sistem Manajemen Aset Berbasis Web Menggunakan Metode Waterfall Untuk Mengoptimalkan Penggunaan Aset Pada PT. Hutama Karya (Persero) - ., Sapardi; Hadikristanto, Wahyu; Kurniadi, Nanang Tedi (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
The utilization of communication and information technology is a suitable step for PT. Hutama Karya (Persero) in managing its assets to ensure optimal asset utilization. Previously, the asset management process relied on manual systems such as handwritten notes and Microsoft Excel as tools for data processing. The solution to effective asset management lies in the implementation of a web-based asset management system application, as the system is computerized, enabling faster and more accurate processes. PT. Hutama Karya (Persero) adopted the waterfall method in developing the asset management system application to ensure a systematic and well-planned development process. The asset management system application was developed using PHP programming language and CodeIgniter 3 framework, resulting in a responsive application interface. The application underwent successful testing, including black box testing to assess its functionality. The results of the testing indicate that the application performs well. With the implementation of this asset management system application, PT. Hutama Karya (Persero) can effectively manage its assets, optimize their utilization, and ensure faster and more accurate asset management processes.